2018
DOI: 10.4153/cjm-2017-016-7
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Classification of Graph C*-algebras over Finite Graphs

Abstract: Abstract. We address the classi cation problem for graph C * -algebras of nite graphs ( nitely many edges and vertices), containing the class of Cuntz-Krieger algebras as a prominent special case. Contrasting earlier work, we do not assume that the graphs satisfy the standard condition (K), so that the graph C * -algebras may come with uncountably many ideals.We nd that in this generality, stable isomorphism of graph C * -algebras does not coincide with the geometric notion of Cuntz move equivalence. However, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(93 citation statements)
references
References 43 publications
5
88
0
Order By: Relevance
“…In a similar way as in the above mentioned cases, this result is a key step in the recent development in the geometric classification of general Cuntz-Krieger algebras and of unital graph C * -algebras ( [ERRS16a,ERRS16b]) as well as in the question of strong classification of general Cuntz-Krieger algebras and of unital graph C * -algebras ( [CRR17,ERRS16b]). In fact, using the results as well as the proof methods of the present paper, these papers close the classification problem for all Cuntz-Krieger algebras and for all unital graph C * -algebras.…”
Section: Introductionmentioning
confidence: 82%
“…In a similar way as in the above mentioned cases, this result is a key step in the recent development in the geometric classification of general Cuntz-Krieger algebras and of unital graph C * -algebras ( [ERRS16a,ERRS16b]) as well as in the question of strong classification of general Cuntz-Krieger algebras and of unital graph C * -algebras ( [CRR17,ERRS16b]). In fact, using the results as well as the proof methods of the present paper, these papers close the classification problem for all Cuntz-Krieger algebras and for all unital graph C * -algebras.…”
Section: Introductionmentioning
confidence: 82%
“…The authors have shown in [ERRS16] that when classifying graph C * -algebras that do not have real rank 0, it can be useful to replace the full filtered K-theory with a version that only looks at gauge invariant ideals. Motivated by this, we develop a version of ideal related algebraic K-theory relative to a sublattice of ideals.…”
Section: Introductionmentioning
confidence: 99%
“…This is used for instance in the proofs of [ERRS16b] to get a classification result. As we are proving a strong classification result, we will need to know more about what this stable isomorphism induces on the reduced filtered K-theory.…”
Section: Cuntz Splice Implies Stable Isomorphismmentioning
confidence: 99%
“…A vertex is a transition state if and only if it is regular and is not the base of a cycle. For a subset S of E 0 , we denote by H(S) the hereditary subset generated by S, and by S the saturation of S (see [ERRS16b,Definition 3.1]).…”
Section: Toke Meier Carlsen Gunnar Restorff and Efren Ruizmentioning
confidence: 99%
See 1 more Smart Citation